Changes in patellar height and patellofemoral alignment following double level osteotomy performed for osteoarthritic knees with severe varus deformity - Yusuke Akaoka; Tomoya Iseki; Ryo Kanto; Shintaro Onishi; Toshiya Tachibana; Keiji Tensho; Shinichi Yoshiya; Hiroshi Nakayama (Elsevier, 2020)
Purpose: To evaluate the effect of double level osteotomy (DLO), a combination of a lateral closed distal femoral osteotomy (LCWDFO) and medial opening wedge high tibial osteotomy (MOWHTO), on patellar height and patellofemoral alignment as compared to those of isolated MOWHTO. Methods: Twenty-six consecutive knees in 26 patients who underwent DLO (DLO group) constituted the study population. For comparative purpose, a control cohort (N: 26) matched for age, sex, and body mass index with the study group were selected from the patients who underwent isolated MOWHTO with an opening gap of more than 10 mm during the same period (MOWHTO group). Patellar height and patellofemoral alignment were assessed on radiographs preoperatively and at 2 years after surgery. For the patellar height, following parameters were measured on a lateral radiograph: Modified Insall-Salvati Index (mISI), modified Caton-Deschamps Index (mCDI), and modified Blackburne-Peel Index (mBPI). In the assessment of patellofemoral alignment, lateral patellar tilt (LPT) and lateral patellar shift (LPS) were measured on a skyline view. The measured values were statistically compared using the Student's t-test. Results: In the DLO group, the patellar height measured by mCDI and mPBPI significantly decreased after surgery. As regards the patellofemoral alignment, LPT significantly decreased with no significant postoperative change detected for LPS. When the amounts of postoperative changes in radiological indices were compared between the DLO and isolated MOWHTO groups, no significant differences were detected for all parameters. Conclusion: DLO induced reduction in patellar height and decreased lateral patellar tilt. Those changes in patellar position and orientation were similarly observed in isolated MOWHTO knees. Although DLO is specifically indicated for knees with severe varus deformity, the two surgical options for correction of varus knee deformity exerted similar influences on patellofemoral biomechanics.